Trans-bordar: entre experiências formativas e princípios que atravessam o vivido com as infâncias - Almeida, Alessandra Menck Machado de (Universidade Federal de São Carlos, 2026)
This research proposes to address the relationships between the training experiences of early childhood education teachers in the municipality of Votorantim/SP and the implementation of the principles of the National Curricular Guidelines for Early Childhood Education (DCNEI), published by the Ministry of Education (Brazil, 2009). Anchored in the concept of experience and a qualitative approach inspired by narrative and (auto)biographical methods, the research mainly engages with the contributions of Walter Benjamin, Jorge Larrosa, and Christine Delory-Momberger, understanding teacher education as a historical, sensitive, and narrative process, influenced by personal, professional, and educational experiences. The methodological path combines bibliographic study, systematic survey of scientific production, application of a questionnaire, and conduction of multifaceted narrative interviews with early childhood education teachers, utilizing different expressive devices and the construction of listening. The teachers’ narratives highlight that the principles of the DCNEI permeate pedagogical practices, revealing both alignments and weaknesses, tensions, and contradictions present in everyday school life. They also show that continuing education is formed in the intertwining of life and profession, marked by experiences that affect, shift, and (trans)form the ways of understanding childhood, play, listening, interactions, and the teaching profession, contributing to the construction of meanings about an education that goes beyond the analysis of programs or educational practices and recognizes the singular, historical, and human movement of the constitution of the teacher and teaching in Early Childhood Education.
Overflowing: between formative experiences and principles that pass through lived childhoods
Keywords: Educação Infantil; Experiências formativas; Narrativas (auto)biográficas; Diretrizes Curriculares Nacionais para a Educação Infantil; Infâncias; Crianças; Early Childhood Education; Formative experiences; (Auto)biographical narratives; National Curriculum Guidelines for Early Childhood Education; Childhoods; Children; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade